CONTRIBUTION OF THE ECONOMIC INDEPENDENCE OF ISLAMIC BOARDING SCHOOL TOWARDS COMMUNITY ECONOMIC EMPOWERMENT - Zikwan, M (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the contribution of the Salafiyah Syafiiyah Islamic boarding school to the economic empowerment of the community. Unlike several other Islamic boarding schools, in terms of fulfilling the needs of 24,713 students, the Salafiyah Syafiiyah Islamic Boarding School still involves the surrounding community as contributors of goods and services. Community involvement in fulfilling the needs of students is a pillar of the economy for both the local community and immigrant communities who aim to earn a living. This study reveals new values in the form of in-depth analysis of the contribution of Islamic boarding schools to the economic empowerment of the community. In previous studies, many studies focused on the educational and social aspects of Islamic boarding schools, the economic empowerment of Islamic boarding schools, but this study provides a new perspective by highlighting the economic role of Islamic boarding schools and their impact on local communities and immigrants.The research method used is qualitative descriptive with a case study approach at the Salafiyah Syafi'iyah Islamic Boarding School in Situbondo. Data were collected through interviews with Islamic boarding school managers, document analysis, and direct observation of economic activities in the Islamic boarding school environment.The results of the study show that community involvement in fulfilling the needs of students is a picture that Islamic boarding schools do not only function as educational centers, but also as centers for driving the economy, especially for local communities. The impact felt by the community is in the form of increased income, especially for traders providing goods and services, creating jobs for immigrants who aim to earn a living.